Sosialisasi Dan Praktik Pemanfaatan Sisa-Sisa Sampah Organik Rumah Tangga Dalam Proses Pembuatan Pupuk Organik Cair (Poc) - Vika Fitranita; IndahOktari Wijayanti; Farisa Retno Wulan (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Socialization and Practice of Utilizing Household Organic Waste Remains in the Process of Making Liquid Organic Fertilizer (POC) in Talang Karet Village. Through this activity it is hoped that it will provide education and understanding to the public to maintain a clean environment and provide education in recycling the remains of organic waste to make it more useful. As for the activity of utilizing organic waste from leftover household vegetables as an alternative medium in the planting process of administering liquid organic fertilizer, it is hoped that it can make the yard of the house a place to grow crops and can help the people of Talang Karet Village in meeting their needs for vegetables for their daily needs. days and can also make it an additional source of income.